An organizational audit of Philippine Science High School (PSHS)-Diliman Campus using the Baldrige education criteria for performance excellence - Legaspi, Julius B. II (University of the Philippines Diliman, 2004)
Just like any organization, the Philippine Science High School (PSHS) wants to be flexible and responsive, able to change in accord with changing circumstances. PSHS envisions itself to be the country's premier high school. It is mandated to lead in the education of the scientifically gifted youth who shall form the base from which leaders and professionals in science and technology can be drawn. It is important to determine whether PSHS still has an educational system that ensures it is producing quality critical mass of science and technology (S&T) personnel. The project aimed to perform a modified Baldrige assessment as an internal improvement effort. Focusing on student learning outcomes and faculty performance, it endeavored to identify potential gaps in key information and focus on key performance requirements and organizational performance results. It hoped to help improve organizational performance practices, capabilities and results. Lastly, it aimed to serve as a working tool for understanding and managing performance and for guiding organizational planning and opportunities for learning. Project results reassure the school that it is still producing quality critical mass of S&T personnel. New graduates end up choosing S&T courses while most alumni find themselves in S&T careers. However, the project cautions that in its effort to make them fulfill their academic potential, it may overlook that it must make them accountable to society for their intellectual gifts. Inculcating values like love of country or the sense of gratitude still need improvement. PSHS graduates also need to learn how to work effectively within a team. These findings point at the necessity to create an environment that caters to the emotional/psychological well-being of its scholars. This highlighted the importance of working with stakeholder groups like parents and alumni. The climate of innovation in PSHS is just right. The dimensions that were in need of greatest improvement were : idea time and idea support. These dimensions pertain to the area of resources. This is quite common for a government institution like PSHS that is often restricted by its budget. It reinforces the challenge that the school must not be deterred if there is not enough time and money to invest to make the environment more innovative. It has to focus its energies in improving the "soft stuff" instead of being discouraged that it cannot procure "hard" resources sooner. The new PSHS Vision Statement focuses on the student anew. Instead of emphasizing the institution, it describes the PSHS core values and overarching qualities desired in PSHS students and graduates. This does not mean that the institution loses significance. It is only assumed that these qualities reside first of all in the PSHS faculty and staff-one cannot give what one does not have. This time, each student is acknowledged to be the unique person that he is and must be treated as such. The school's role is to help each one discover himself (character traits, strengths, weaknesses) and develop his potentials to the extent possible within the context of the special science curriculum. This self-knowledge will assist him in selecting the most appropriate paths in the university and in his professional undertakings. It is hoped that the fulfillment of this vision would lead to happy and fruitful lives of its graduates.